Serologic and bioinformatics analysis of the Brucella cross reacting antigens - Pourmahdi Borujeni, M; Khosravi, M; Gharibi, D; Khademi Moghadam, F; Yousefinejad, S (Journal of the Hellenic Veterinary Medical Society, 2024)
Brucella species are the cause of a zoonotic disease in humans and various species of animals. The accurate diagnosis of brucellosis could limit the prevalence of the disease. The current study aimed to identify the cross reacting antigens among Brucella and some of the bacteria that possessing antigens of this sort. A total of 36 positive and negative sheep serum samples in Rose Bengal test, enrolled in the current research. The antibody titers against Brucella abortus, Salmonella typhimurium, Pasteurella multocida, Yersinia enterocolitica, Proteus vulgaris and Escherichia coli were determined using the indirect and absorbed indirect ELISA. The cross reacting antigens were defined using the bioinformatics and western-blotting assay. The positive samples have significant IgG antibody titer against all of the tested bacterial strains. There was a significant difference (P≤0.05) between the results of the direct and absorbed ELISA for delineating the anti- Brucella antibodies. Immunoblot assays revealed reactivity of the antibodies with the several protein bands in the other bacteria. Also, there was a significant correlation between % sequence and the structural identity (P≤0.001). Two proteins including Cu/Zn superoxide dismutase and methionine aminopeptidase of the mentioned bacteria showed a significantly higher similarity to Brucella proteins (P ≤0.001). These observations suggested the existence of variable IgM and IgG antibodies titer against other bacteria in Brucella positive samples; additionally, the anti-Brucella antibody in each of the positive samples had different cross reactivity against the common antigens of the other bacteria.